Chemical profile of Leaves of Magana and NASE3 Varieties of Manihot esculentum Crantz Harvested from Bukedea District, Eastern Uganda - Kayendeke, Joweria; Ssenku, Jamilu Edrisa; Kibedi, Cabral Bilal; Walusansa, Abdul; Wikantyasning, Erindyah Retno; Sari, Morita (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Cassava leaves are widely consumed worldwide, particularly in the Bukedea district of Uganda, for food, medicine, and fodder. The existing correlation between high cassava leaf consumption and organ toxicity and failure remains poorly established within the Bukedea district.  This investigation aimed to evaluate the phytochemical composition and toxicity profiles of cassava leaves consumed in the Bukedea District.  An ethnobotanical survey was conducted among 60 participants selected from three villages in Bukedea, using a pretested questionnaire and an interview guide.  The qualitative and quantitative phytochemical compositions of the ethanolic and aqueous extracts of NASE3 and Magana varieties were determined by High-Performance Liquid Chromatography (HPLC).  Results were analyzed using R version 4.3.2 and presented as mean ± SD in tables, Graphical HPLC reports, and figures generated by GraphPad Prism @9.00.  An ethno-botanical survey revealed that NASE3 and Magana are the most commonly consumed varieties of cassava leaves, and highlighted their side effects.  Qualitatively, Magana had significantly more phytochemicals than NASE3, which mainly consisted of toxic compounds (p < 0.0001).  According to quantitative HPLC graphic reports, Magana had higher phytochemical concentrations than NASE3 (p < 0.0001).  No significant difference (p = 0.62-1.00, p > 0.0001) in the mean concentration of the same phytochemical ingredient between the two extracts of each cassava leaf variety was exhibited. In conclusion, communities in Bukedea District are vulnerable to toxic phytochemicals from consuming NASE3 and Magana cassava leaves.  Further studies on sub-acute and sub-chronic toxicity, the development of non-toxic cassava varieties, and chemical characterization are warranted.